A Synthetic Overview of Enones Aziridination. Issue 22 (9th June 2022) - Chandra, Dinesh; Kumar, Puneet; Yadav, Ajay K.; Kumar, Ganesh; Jat, Jawahar L.
Abstract: Aziridines are an important class of synthetic intermediates that are widely used in the synthesis of useful compounds and intermediates found in pharmaceuticals, natural products, and other functional materials. Several compounds with the aziridine ring system exhibit significant biological activity as well. Consequently, the synthesis of aziridines has been the focus of intense research over the last two decades. Despite numerous successful methods, no review article exclusively on Enone aziridination has been published to date. Therefore, the up‐to‐date developments in the synthesis of aziridines from enones, which are convenient synthetic precursors, by nucleophilic addition reactions are described with advantages, limitations, and mechanistic pathways. Abstract : Aziridines are synthetically useful intermediates due to their strained ring system. Aziridination of enones would provide synthetic intermediates with two valuable functional groups quickly. Herein, we have described the latest developments in the aziridination of the enone substrates. The methods to provide aziridinated enones where the nitrogen of the aziridine ring is unprotected as well as protected are described in this article. Many of these methods provide aziridines stereoselectively which would make the products synthetically valuable.